2018
DOI: 10.1088/1361-6528/aaa84d
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamics model for morphology prediction of aluminum nano crystals fabricated by the inert gas condensation method

Abstract: The purpose of this study is to provide scientific guidance for the morphological control of nanoparticle synthesis using the gas phase method. A universal thermodynamics model is developed to predict the morphology of nanoparticles fabricated using the inert gas condensation method. By using this model, the morphologies of aluminum nanocrystals are predicted under various preparation conditions. There are two types of energy that jointly determine the formation of nanoparticle morphology-Gibbs free energy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Researchers have shown that the omission is valid for particles with diameters exceeding approximately 10 nm because the edges play a minor role in the particles’ equilibrium shape . For smaller nanoparticles it is ubiquitously believed that edge energies are a significant contributor to the total energies and should be considered in thermodynamic morphology models. …”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that the omission is valid for particles with diameters exceeding approximately 10 nm because the edges play a minor role in the particles’ equilibrium shape . For smaller nanoparticles it is ubiquitously believed that edge energies are a significant contributor to the total energies and should be considered in thermodynamic morphology models. …”
Section: Introductionmentioning
confidence: 99%